1965
DOI: 10.1530/acta.0.0480220
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Lactogenic Hormone Release During Onset of Pseudopregnancy in Intact Rats

Abstract: The release of lactogenic hormone (LGH) was studied at the onset of pseudopregnancy in 90 rats. The LGH-content of the pituitary glands was determined by the pigeon crop sac assay. Glass rod stimulation of the cervix during vaginal oestrus was followed by a significant decrease in the LGH-content of the pituitary glands, thus demonstrating a correlation between LGH-release and beginning pseudopregnancy. Anaesthesia by Nembutal almost prevented this effect of cervical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
1

Year Published

1967
1967
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
(2 reference statements)
2
6
1
Order By: Relevance
“…Pituitary prolactin concentration did not decrease until 24 hr after the induction of pseudopregnancy. This is contrary to the findings of Herlyn et d. (3) who observed a significant decrease in pituitary prolactin content within 30 min after glass rod stimulation of the cervix. The method of stimulation or the strain of rats may have made the difference; however, Taleisnik et al (8) did not find any evidence of LH release in rats 1 hr after a glass rod stimulation of cervix although normal mating resulted in a significant discharge of the hormone.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Pituitary prolactin concentration did not decrease until 24 hr after the induction of pseudopregnancy. This is contrary to the findings of Herlyn et d. (3) who observed a significant decrease in pituitary prolactin content within 30 min after glass rod stimulation of the cervix. The method of stimulation or the strain of rats may have made the difference; however, Taleisnik et al (8) did not find any evidence of LH release in rats 1 hr after a glass rod stimulation of cervix although normal mating resulted in a significant discharge of the hormone.…”
contrasting
confidence: 99%
“…The data suggest that prolactin in rats may be involved in Since the original work with amphenone ( 1) and related compounds such as metyrapone, a large number of substances were shown to modify the pattern of steroidogenesis in the adrenal [Refs. (2,3)]. One of these, designated Su-10603, synthesized by Bencze and Barsky (4) had considerable activity as an adrenal 17~-hydroxylase inhibitor both in vivo and in vitro (5-7).…”
mentioning
confidence: 99%
“…In contrast to the LH results, paced mating did not selectively increase PRL over levels seen in non-paced and mounts-only females. Acute PRL increases (within 15 to 30min) have becn seen in mated (7) and cervically-stimulated (3,30) females, while in other studies, no acute PRL response has been observed (1 3, 15). In the present study.…”
Section: Matingmentioning
confidence: 77%
“…In rats, a rise in the plasma concentration of L H occurs within 5-10 min after coitus, and a slight rise in the FSH content of the pituitary is seen 1 hr after copulation (1). Pituitary L T H falls within 30 min after cervical stimulation ( 2 ) , whereas plasma progesterone rises 24 hr after mating (3).…”
mentioning
confidence: 99%
“…The nonprotein sulfhydryl (NPSH) level in the liver of mice administered endotoxin has been shown to decrease by nearly 25% within 2 hr and to fall to about 45% of normal in 18 hr (1,2 ) . A similar rapid decrease in the liver NPSH has been reported following a number of other stress conditions, such as, scalding or ligature of hind legs ( 2 ) .…”
mentioning
confidence: 99%